2007
DOI: 10.1097/01.aids.0000300540.12849.86
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cinderella myth: intrahousehold differences in child wellbeing between orphans and non-orphans in Amajuba District, South Africa

Abstract: We found no statistically significant differences in most education, health and labour outcomes between orphans and the non-orphans with whom they live. Paternal orphans are more likely to be behind in school, and recent mobility has a positive effect on schooling outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 11 publications
1
37
1
Order By: Relevance
“…It has been suggested this is because the poorest households are less likely to invite orphans to live with them (Bicego et al, 2003). Another research group suggested that the movement of orphans is ''strategic'' in that they are sent to live with relatives known to be capable of caring for them (Parikh et al, 2007). It is possible that a similar situation is occurring among the Luo households in this study and that orphans are only invited or sent to live with well-off relatives.…”
Section: Discussionmentioning
confidence: 74%
“…It has been suggested this is because the poorest households are less likely to invite orphans to live with them (Bicego et al, 2003). Another research group suggested that the movement of orphans is ''strategic'' in that they are sent to live with relatives known to be capable of caring for them (Parikh et al, 2007). It is possible that a similar situation is occurring among the Luo households in this study and that orphans are only invited or sent to live with well-off relatives.…”
Section: Discussionmentioning
confidence: 74%
“…Some studies find that there is no difference between the school attendance of orphans and non-orphans (Yamano et al 2006;Parikh et al 2007). Orphanhood either depresses or increases schooling depending on the country 7 (Ainsworth and Filmer 2002;Bennell 2005;Guo et al 2012).…”
Section: Prior Researchmentioning
confidence: 99%
“…Using DHS and other survey data for Ghana, Kenya, Malawi, Niger, Tanzania, and Zimbabwe, earlier research shows that orphans are a grade level behind non-orphans (Bicego et al 2003;Guo et al 2012;Kidman et al 2012). Net of household wealth, the risk of being behind is greater for paternal and double orphans than maternal orphans and non-orphans (Bicego et al 2003;Case et al 2004;Bennell 2005;Parikh et al 2007). An exception is Botswana, where maternal orphans are most likely to be behind (Bennell 2005).…”
Section: Prior Researchmentioning
confidence: 99%
“…Researchers posited that all children in the household suffer the same contact information, economic and other deprivations resulting from spreading resources more thinly as a 'coping' response to the epidemic (Barnett and Whiteside, 2007). Parikh et al (2007) also found no statistically significant differences in most education, health and labour outcomes between orphans and the non-orphans with whom they live (cohort of 197 recent orphans and 528 non-orphans aged 9-16 years) in KwaZulu Natal, South Africa.…”
Section: Literature Reviewmentioning
confidence: 77%